Manufacturing method of aluminum alloy material and manufacturing method of clad material

By using waste materials and controlling alloy composition, the problems of poor welding performance and high carbon emissions of aluminum alloy sandwich materials are solved, and efficient resource recycling and low-carbon production are achieved.

JP7654878B1Active Publication Date: 2025-04-01KOBE STEEL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024120974
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-04-01
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

In the prior art, it is difficult to ensure excellent welding performance when manufacturing aluminum alloy materials and aluminum alloy sandwich materials. At the same time, due to the large power consumption of new aluminum materials, carbon emissions are increased and recycling is difficult.

Method used

By using waste materials when producing aluminum alloy interlayer materials and waste from waste automobile heat exchangers as raw materials, the casting process is used to synthesize aluminum alloy materials, and the composition and recovery of the alloy are controlled to ensure the high welding performance of the alloy.

Benefits of technology

The high welding performance of aluminum alloy sandwich materials has been achieved, reducing the demand for new aluminum materials, reducing carbon emissions, and improving the recycling rate of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654878000001
    Figure 0007654878000001
  • Figure 0007654878000002
    Figure 0007654878000002
  • Figure 0007654878000003
    Figure 0007654878000003
Patent Text Reader

Abstract

A method for producing an aluminum alloy material, which can easily produce an aluminum alloy material having excellent brazeability, is provided. [Solution] The method for manufacturing an aluminum alloy material includes a selection step of selecting only aluminum alloy scrap material having a Mg content of 0.10 mass% or less as a casting raw material A, a casting step of casting an ingot using the casting raw material A and the casting raw material B for addition, and a molding step of molding the ingot into an aluminum alloy material having a predetermined composition and a solidus temperature of 600° C. or more. The recycling rate, which indicates the mass ratio of the casting raw material A to the total mass of the ingot, is R (%), and the Si content in the casting raw material A is [Si] in mass%. A , between the selection process and the casting process, the formula (1): [Si] A The recycle rate R is determined so that the value calculated by ×R / 100 is 0.50 or more and 1.10 or less. The casting raw material A contains predetermined amounts of Si and Zn.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an aluminum alloy material, and a method for producing a clad material using the aluminum alloy material. [Background technology]

[0002] In recent years, achieving carbon neutrality has become an issue for society as a whole, and various methods for solving the above issue have been considered. For example, in view of resource depletion, recycling of various things has progressed, and recycling of metals, which are consumed in large quantities, has been carried out for some time. In addition, in the field of aluminum alloy materials used in heat exchangers for automobiles, there is a demand for resource reuse. In particular, aluminum consumes a large amount of electricity and emits CO2 when producing new ingots. Therefore, by reducing the amount of new ingots used through recycling, it is possible to significantly reduce CO2 emissions during the production of aluminum alloy materials.

[0003] However, because automotive heat exchangers are made of clad materials that are laminated with sacrificial anode materials that impart corrosion resistance to the surface of aluminum alloy core materials and brazing materials that impart brazing properties, recycling clad materials to produce core materials can result in a deterioration of the properties of the core materials, making it more difficult to reuse clad materials used in heat exchangers than recycling single-layer aluminum alloy materials.

[0004] Patent Document 1 discloses a method for producing an aluminum alloy material using a casting raw material containing a predetermined content of scraps of automotive heat exchangers in which clad materials are used and / or scraps of aluminum alloy clad materials used in automotive heat exchangers. The production method described in Patent Document 1 includes a casting step of casting an aluminum alloy ingot A having a predetermined composition using the casting raw material, and the natural electrode potential of the resulting aluminum alloy part A is specified. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 7275336 Summary of the Invention [Problem to be solved by the invention]

[0006] However, even when the manufacturing method of the aluminum alloy material described in the above Patent Document 1 is used, the brazeability is not sufficiently excellent. In addition, the above Patent Document 1 describes the use of a casting raw material containing scrap made of an aluminum alloy containing one or more elements selected from the group consisting of Si, Fe, Cu, Mn, Mg, and Zn in a predetermined amount. However, the above Patent Document 1 does not specify the essential elements in the scrap, and the composition of the casting raw material is not described in the examples, so that the effect cannot be fully confirmed.

[0007] The present invention has been made in consideration of such problems, and aims to provide a method for producing an aluminum alloy material and a method for producing a clad material, which can easily produce an aluminum alloy material for a clad material having excellent brazing properties by using scraps generated during the manufacturing process of the clad material and discarded aluminum heat exchangers as raw materials for new heat exchanger materials, and can also easily produce a clad material having excellent brazing properties, thereby reducing the amount of new metal used and significantly reducing CO2 emissions. [Means for solving the problem]

[0008] The above object can be achieved by the following method for producing an aluminum alloy material according to the present invention (1).

[0009] (1) A method for producing an aluminum alloy material, comprising the steps of: producing an aluminum alloy material using a casting raw material A and a casting raw material B; a selection step of selecting only aluminum alloy scrap material having a Mg content of 0.10 mass% or less from at least one of scrap of automotive heat exchangers using clad materials and scrap of aluminum alloy clad materials used for automotive heat exchangers, as the casting raw material A; A casting process for casting an ingot using the casting raw material A and the casting raw material B for addition; and a molding step of molding the ingot into an aluminum alloy material having a solidus temperature of 600°C or more. The recycling rate, which represents the mass ratio of the casting raw material A to the total mass of the ingot, is R (%), and the Si content in the casting raw material A is [Si] in mass%. A , when expressing Between the selection step and the casting step, Formula (1): [Si] A ×R / 100 The value calculated by is 0.50 or more and 1.10 or less, A recycling rate determination step of determining a recycling rate R so that The casting step is a step of casting the ingot using the casting raw material A in an amount of R (%) relative to the total mass of the ingot and the casting raw material B in an amount of (100-R) (%) relative to the total mass of the ingot, The casting raw material A is, with respect to the total mass of the casting raw material A, Si: 0.50 mass% or more, and Zn: 0.10% by mass or more, Contains at least one element selected from Fe: 0.10% by mass or more, Cu: 0.08% by mass or more, and Mn: 0.50% by mass or more; The aluminum alloy material is Si: 0.50 mass% or more and 1.10 mass% or less, Fe: 0.10% by mass or more and 1.00% by mass or less, Cu: 0.08% by mass or more and 0.80% by mass or less, Mn: 0.90% by mass or more and 1.80% by mass or less, and Zn: 0.10% by mass or more and 1.00% by mass or less; Mg: 0.10% by mass or less, Ti: 0.30% by mass or less, Cr: 0.30% by mass or less, Zr: 0.30% by mass or less, V: 0.30% by mass or less, Ca: 0.30% by mass or less, Sc: 0.20% by mass or less, Ni: 0.30% by mass or less, 1. A method for producing an aluminum alloy material, comprising: Mo: 0.30 mass % or less, with the balance being Al and unavoidable impurities.

[0010] The method for producing the aluminum alloy material of the present invention is preferably the following (2) to (5).

[0011] (2) The method for producing an aluminum alloy material according to (1), wherein the recycling rate R is 20% or more and 50% or less.

[0012] (3) The method for producing an aluminum alloy material according to (1) or (2), wherein the casting raw material B does not contain Si.

[0013] (4) The method for producing an aluminum alloy material according to any one of (1) to (3), wherein the casting raw material B does not contain Zn.

[0014] (5) The method for producing an aluminum alloy material according to any one of (1) to (4), wherein the casting raw material A contains Zn: 1.00 mass % or less.

[0015] The above object can also be achieved by the following method for producing a clad material according to the present invention (6).

[0016] (6) A method for producing a clad material comprising an aluminum alloy material produced by the method according to any one of (1) to (5), The aluminum alloy material is used as a core aluminum alloy material, A method for producing a clad material, comprising laminating the aluminum alloy material for a core material and at least one type of functional aluminum alloy material to produce a clad material.

[0017] The method for producing the clad material of the present invention is preferably the following (7) to (11).

[0018] (7) The method for producing a clad material according to (6), wherein the functional aluminum alloy material includes at least one of an aluminum alloy material for brazing material and an aluminum alloy material for sacrificial anode material.

[0019] (8) The aluminum alloy material for brazing filler metal is Si: 2.50% by mass or more and 13.00% by mass or less, and Fe: 0.05% by mass or more and 1.00% by mass or less; Zn: 5.50% by mass or less, Mn: 1.00% by mass or less, Cu: 1.00% by mass or less, Cr: 0.30% by mass or less, Ti: 0.30% by mass or less, Zr: 0.30% by mass or less, V: 0.30% by mass or less, Ca: 0.30% by mass or less, Sc: 0.20% by mass or less, Ni: 0.30% by mass or less, Mo: 0.30% by mass or less, Sb: 0.30% by mass or less, Sr: 0.10% by mass or less, The method for producing a clad material according to (7), characterized in that Na is 0.10 mass % or less, with the balance being Al and unavoidable impurities.

[0020] (9) The aluminum alloy material for the sacrificial anode material is Zn: 0.50 mass% or more and 6.00 mass% or less, Si: 0.05% by mass or more and 1.50% by mass or less, and Fe: 0.05% by mass or more and 2.00% by mass or less; Mg: 3.00% by mass or less, Mn: 1.80% by mass or less, Cu: 0.50% by mass or less, Cr: 0.30% by mass or less, Ti: 0.30% by mass or less, Zr: 0.30% by mass or less, V: 0.30% by mass or less, Ca: 0.30% by mass or less, Sc: 0.20% by mass or less, Ni: 0.30% by mass or less, The method for producing a clad material according to (7) or (8), characterized in that Mo is 0.30 mass % or less, with the balance being Al and unavoidable impurities.

[0021] (10) The method for producing a clad material according to any one of (7) to (9), characterized in that the clad material has a structure in which the aluminum alloy material for brazing material / the aluminum alloy material for core material / the aluminum alloy material for brazing material or the aluminum alloy material for sacrificial anode material are laminated in this order.

[0022] (11) The clad material includes an intermediate layer between the core aluminum alloy material and the functional aluminum alloy material, The intermediate layer is Si: 0.05% by mass or more and 1.50% by mass or less, and Fe: 0.05% by mass or more and 2.00% by mass or less; Zn: 6.00% by mass or less, Mn: 1.80% by mass or less, Cu: 1.00% by mass or less, Cr: 0.30% by mass or less, Ti: 0.30% by mass or less, Zr: 0.30% by mass or less, V: 0.30% by mass or less, Ca: 0.30% by mass or less, Sc: 0.20% by mass or less, Ni: 0.30% by mass or less, The method for producing a clad material according to any one of (6) to (10), characterized in that Mo is 0.30 mass % or less, with the balance being Al and unavoidable impurities. Effect of the Invention

[0023] According to the manufacturing method of the aluminum alloy material of the present invention, scrap of automotive heat exchangers and scrap of aluminum alloy clad material for automotive heat exchangers can be reused to manufacture an aluminum alloy material for clad material having excellent brazing property, thereby reducing the amount of new metal used and significantly reducing CO2 emissions.

[0024] Furthermore, according to the method for producing a clad material of the present invention, since the aluminum alloy material having the above-mentioned excellent properties is used as an aluminum alloy material for the core material, a clad material with excellent brazing properties can be produced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] As a result of intensive research, the inventors of the present application have found that controlling the solidus temperature of an aluminum alloy material produced using scrap is important for obtaining excellent brazing properties. In order to avoid the deterioration of brazing properties due to the decrease in activity of the flux during brazing, it has been found that it is effective to select only scrap material having a Mg content of 0.1 mass% or less as the casting raw material A, determine the recycling rate based on the Si content in the casting raw material A, and produce an aluminum alloy material of a desired composition. Hereinafter, a manufacturing method of an aluminum alloy material according to an embodiment of the present invention will be described in detail.

[0026] [Method of manufacturing aluminum alloy materials] The method for producing an aluminum alloy material according to this embodiment is a method for producing an aluminum alloy material by using a casting raw material A and a casting raw material B.

[0027] <Selection process> From at least one of scraps of automotive heat exchangers using clad materials and scraps of aluminum alloy clad materials used in automotive heat exchangers, only aluminum alloy scrap materials having a Mg content of 0.1 mass % or less are selected to be used as the casting raw material A. Since Mg is an element that reacts with flux during brazing and reduces the activity of the flux, by selecting only aluminum alloy scrap materials having a Mg content of 0.1 mass % or less to be used as the casting raw material A, it is possible to easily produce an aluminum alloy material having excellent brazability even when scrap materials are reused.

[0028] In this specification, "scrap from automotive heat exchangers using clad material" refers to scrap generated when automotive heat exchangers using clad material are discarded. Also, "scrap from aluminum alloy clad material used in automotive heat exchangers" refers to both scrap generated during the manufacture of aluminum alloy clad material and scrap from clad material generated during the manufacture of automotive heat exchangers. In this specification, these are sometimes simply referred to as "scrap."

[0029] If an aluminum alloy material is manufactured by selecting only aluminum alloy scrap material having a Mg content exceeding 0.1% by mass, it is necessary to increase the amount of the casting raw material B used in order to obtain an aluminum alloy material containing a desired Mg content. As a result, it is not possible to reduce the amount of new ingots used, and CO2 emissions increase. Therefore, in the selection process, only aluminum alloy scrap material having a Mg content of 0.1% by mass or less relative to the total mass of the aluminum alloy scrap material (casting raw material A) is selected. In addition, it is preferable to select only aluminum alloy scrap material having a Mg content of 0.05% by mass or less, more preferable to select only aluminum alloy scrap material having a Mg content of less than 0.05% by mass, and even more preferable to select only aluminum alloy scrap material that does not substantially contain Mg. Note that "substantially does not contain Mg" includes the inclusion of Mg at the level of unavoidable impurities contained in the ingots of the raw material of the aluminum alloy clad material generally used for automotive heat exchangers.

[0030] <Recycling rate determination process> In this embodiment, in the casting process described below, an ingot is cast using the casting raw material A and the casting raw material B for addition based on the recycle rate. Therefore, in this process, the recycle rate is determined based on the Si content in the casting raw material A. Specifically, the recycle rate representing the mass ratio of the casting raw material A to the total mass of the ingot obtained by the casting process is R (%), and the Si content in the casting raw material A is [Si] in mass%. A , the recycle rate R is determined so that the value calculated by the following formula (1) is 0.50 or more and 1.10 or less. The value calculated by the following formula (1) is the Si content in the aluminum alloy material when the casting raw material B used in the subsequent casting process does not contain Si.

[0031] Formula (1): [Si] A ×R

[0032] By determining the recycle rate so as to obtain a target Si content based on the Si content in the casting raw material A, even if a casting raw material B not containing Si is used in the casting process, the Si content in the aluminum alloy material can be adjusted to a desired range.

[0033] <Casting process> After the recycle rate determination process, an ingot is cast using the casting raw material A and the additional casting raw material B. Specifically, an ingot is cast using the casting raw material A of R (%) relative to the total mass of the ingot to be obtained, and the casting raw material B of (100-R) (%) relative to the total mass of the ingot.

[0034] <Molding process> The ingot cast in the above casting step is molded to mold an aluminum alloy material having a solidus temperature of 600°C or higher. If the solidus temperature of the molded aluminum alloy material is lower than 600°C, the aluminum alloy material melts during brazing of the final product, resulting in reduced brazability. Therefore, in this embodiment, the composition of the aluminum alloy material is controlled so that the solidus temperature of the resulting aluminum alloy material falls within the following range.

[0035] (Solidus temperature: 600℃ or more) If the solidus temperature of the aluminum alloy material produced by the manufacturing method according to the present embodiment is less than 600°C, the aluminum alloy material melts during brazing, and the brazing property is reduced. If the solidus temperature is high, the furnace temperature can be set high, and the Si content in the brazing material can be reduced. Therefore, the solidus temperature of the aluminum alloy material is set to 600°C or higher, preferably 605°C or higher, and more preferably 610°C or higher. From the viewpoint of recyclability, it is preferable to set the target value of the solidus temperature low, since it is easy to control each component.

[0036] Hereinafter, the chemical components of the casting raw material A used and the aluminum alloy material to be produced and the reasons for limiting the contents thereof will be described in detail. First, the chemical components in the casting raw material A will be described.

[0037] <Casting material A> (Si: 0.50% by mass or more) Si is an element that improves the strength of an aluminum alloy material by dissolving in the parent phase or forming an Al-Mn-Si intermetallic compound together with Mn. As described above, in this embodiment, the recycle rate is determined based on the Si content of the scrap (casting raw material A), because the scrap generally contains a large amount of Si, which is a brazing material component. If the Si content of the casting raw material A is less than 0.50 mass%, the Si content of the aluminum alloy material decreases regardless of the recycle rate, and the effect of improving the strength of the aluminum alloy material cannot be sufficiently obtained. Therefore, the Si content of the casting raw material A is set to 0.50 mass% or more, preferably 0.60 mass% or more, and more preferably 0.70 mass% or more, based on the total mass of the casting raw material A.

[0038] (Zn: 0.10% by mass or more) Scrap generally contains Zn, which is a component derived from the sacrificial anode material, and the average Zn content in the scrap is about 0.25 to 0.80 mass%. Therefore, the lower limit of the Zn content in the casting raw material A is determined based on the lower limit of the Zn contained in the casting raw material A as a component of the sacrificial anode material. If the Zn content in the casting raw material A is 0.10 mass% or more, a general clad material for automotive heat exchangers can be used regardless of the recycling rate. Therefore, the Zn content in the casting raw material A is 0.10 mass% or more, preferably 0.12 mass% or more, and more preferably 0.15 mass% or more, based on the total mass of the casting raw material A.

[0039] On the other hand, if the Zn content in the casting raw material A is too high, the Zn content in the aluminum alloy material also increases, which affects the solidus temperature depending on the recycling rate. Specifically, if the Zn content in the casting raw material A is 1.00 mass% or less, the drop in the solidus temperature can be suppressed regardless of the recycling rate. Therefore, the Zn content in the casting raw material A is preferably 1.00 mass% or less, more preferably 0.70 mass% or less, even more preferably 0.50 mass% or less, and particularly preferably 0.30 mass% or less, based on the total mass of the casting raw material A.

[0040] The casting raw material A used in this embodiment contains at least one element selected from Fe, Cu and Mn in addition to the above-mentioned Si and Zn in the ranges shown below.

[0041] (Fe: 0.10% by mass or more) Fe is an element that easily forms intermetallic compounds of a size that can become recrystallization nuclei. Regardless of whether scrap is used or not, Fe is contained in commonly used aluminum alloy materials, so the lower limit of the Fe content in the scrap is not particularly limited. However, if the Fe content in the casting raw material A is 0.10 mass% or more, it is not necessary to use the casting raw material B with an extremely small Fe content, and an aluminum alloy material with a desired Fe content can be obtained. Therefore, when using the casting raw material A containing Fe, it is preferable to use scrap (casting raw material A) with an Fe content of 0.10 mass% or more relative to the total mass of the casting raw material A.

[0042] (Cu:0.08% by mass or more) Scrap generally contains Cu, and the average Cu content in the scrap is about 0.10 to 0.60 mass%. Therefore, the lower limit of the Cu content in the scrap is not particularly limited, but when using a casting raw material A containing Cu, it is preferable to use scrap (casting raw material A) in which the Cu content relative to the total mass of the casting raw material A is 0.08 mass% or more. It is more preferable to use scrap in which the Cu content in the casting raw material A is 0.10 mass% or more, more preferably 0.20 mass% or more, and particularly preferably 0.30 mass% or more.

[0043] (Mn: 0.50% by mass or more) Mn is an element that improves the strength of an aluminum alloy material by dispersion strengthening by forming an Al-Mn-Si intermetallic compound together with Si, and by solid-solution strengthening by dissolving in the aluminum parent phase. In this embodiment, Mn may be contained in the casting raw material B in order to improve the strength of the aluminum alloy material. For this reason, the lower limit of the Mn content in the scrap is not particularly limited, but when using a casting raw material A containing Mn, it is preferable to use scrap (casting raw material A) in which the Mn content relative to the total mass of the casting raw material A is 0.50 mass% or more. In addition, it is more preferable to use scrap in which the Mn content in the casting raw material A is 0.90 mass% or more, and even more preferable to use scrap in which the Mn content is 1.00 mass% or more.

[0044] Next, the chemical components of the aluminum alloy material produced by the production method according to the embodiment of the present invention, the reasons for limiting the contents thereof, and a preferable recycling rate will be described.

[0045] <Aluminum alloy material> (Si: 0.50 mass% or more and 1.10 mass% or less) As described above, Si is an element that improves the strength of an aluminum alloy material by dissolving in the parent phase or forming an Al-Mn-Si intermetallic compound together with Mn. In this embodiment, the recycle rate is determined based on the Si content in the casting raw material A so that the Si content in the aluminum alloy material falls within a predetermined range. Therefore, an aluminum alloy material having a desired Si content can be obtained without adjusting the Si content by the casting raw material B.

[0046] If the Si content in the aluminum alloy material is less than 0.50 mass%, the effect of improving the strength of the aluminum alloy material cannot be sufficiently obtained. Therefore, the Si content in the aluminum alloy material is set to 0.50 mass% or more, preferably 0.60 mass% or more, and more preferably 0.65 mass% or more, based on the total mass of the aluminum alloy material. On the other hand, if the Si content in the aluminum alloy material exceeds 1.10 mass%, the solidus temperature of the aluminum alloy material decreases, and melting occurs during brazing. Therefore, the Si content in the aluminum alloy material is set to 1.10 mass% or less, preferably 1.05 mass% or less, and more preferably 1.00 mass% or less, based on the total mass of the aluminum alloy material.

[0047] (Fe: 0.10 mass% or more and 1.00 mass% or less) Fe is an element that easily forms an intermetallic compound of a size that can become a recrystallization nucleus. Since Fe is generally contained in the casting raw material A, in order to make the Fe content in the aluminum alloy material less than 0.10 mass%, it is necessary to use high-purity aluminum ingot (casting raw material B), which increases the manufacturing cost. Therefore, the Fe content in the aluminum alloy material is 0.10 mass% or more, preferably 0.12 mass% or more, and more preferably 0.15 mass% or more, based on the total mass of the aluminum alloy material. On the other hand, if the Fe content in the aluminum alloy material exceeds 1.00 mass%, the crystal grain size after brazing becomes fine, and brazing material diffusion occurs, resulting in a decrease in erosion resistance. Therefore, the Fe content in the aluminum alloy material is 1.00 mass% or less, preferably 0.80 mass% or less, and more preferably 0.60 mass% or less, based on the total mass of the aluminum alloy material.

[0048] (Cu: 0.08 mass% or more and 0.80 mass% or less) Scrap generally contains Cu. Therefore, in order to make the Cu content in the aluminum alloy material less than 0.08 mass%, it is necessary to use high-purity aluminum ingot (casting raw material B), which increases the manufacturing cost. In addition, if the Cu content in the aluminum alloy material is less than 0.08 mass%, the corrosion resistance of the aluminum alloy material decreases. Therefore, the Cu content in the aluminum alloy material is set to 0.08 mass% or more, preferably 0.10 mass% or more, more preferably 0.20 mass% or more, and even more preferably 0.30 mass% or more, based on the total mass of the aluminum alloy material. On the other hand, if the Cu content in the aluminum alloy material exceeds 0.80 mass%, the solidus temperature decreases and melting occurs during brazing. Therefore, the Cu content in the aluminum alloy material is set to 0.80 mass% or less, preferably 0.70 mass% or less, and more preferably 0.65 mass% or less, based on the total mass of the aluminum alloy material.

[0049] (Mn: 0.90 mass% or more and 1.80 mass% or less) Mn is an element that has the effect of improving the strength of an aluminum alloy material. If the Mn content in the aluminum alloy material is less than 0.90% by mass, the effect of improving the strength cannot be sufficiently obtained. In addition, if the Mn content in the aluminum alloy material is less than 0.90% by mass, the solidus temperature also rises and the brazing property deteriorates. Therefore, the Mn content in the aluminum alloy material is 0.90% by mass or more, preferably 1.00% by mass or more, and more preferably 1.05% by mass or more, based on the total mass of the aluminum alloy material. On the other hand, if the Mn content in the aluminum alloy material exceeds 1.80% by mass, a giant intermetallic compound is easily formed during casting, which reduces the plastic workability. Therefore, the Mn content in the aluminum alloy material is 1.80% by mass or less, preferably 1.70% by mass or less, and more preferably 1.65% by mass or less, based on the total mass of the aluminum alloy material.

[0050] (Zn: 0.10 mass% or more and 1.00 mass% or less) In general, scrap contains Zn, which is a component derived from the sacrificial anode material. Therefore, in order to make the Zn content in the aluminum alloy material less than 0.10 mass%, it is necessary to use high-purity aluminum ingot (casting raw material B), which increases the manufacturing cost. Therefore, the Zn content in the aluminum alloy material is 0.10 mass% or more, preferably 0.12 mass% or more, and more preferably 0.15 mass% or more, based on the total mass of the aluminum alloy material. On the other hand, if the Zn content in the aluminum alloy material exceeds 1.00 mass%, the solidus temperature decreases. Therefore, the Zn content in the aluminum alloy material is 1.00 mass% or less, preferably 0.50 mass% or less, and more preferably 0.30 mass% or less, based on the total mass of the aluminum alloy material.

[0051] (Mg: 0.10% by mass or less) Since Mg is an element that reacts with flux during brazing and reduces brazing properties, it is preferable that the Mg content in the aluminum alloy material is small. In this embodiment, as described above, only aluminum alloy scrap material with a Mg content of 0.1 mass% or less is selected as the casting raw material A, so it is preferable that the casting raw material B does not contain Mg either. If the Mg content in the aluminum alloy material exceeds 0.10 mass%, the brazing properties are reduced. Therefore, the Mg content in the aluminum alloy material is 0.10 mass% or less, preferably 0.05 mass% or less, and more preferably 0 mass% with respect to the total mass of the aluminum alloy material.

[0052] (Cr: 0.30 mass% or less) Cr is an element that improves the strength of the aluminum alloy material by solid solution strengthening, and also precipitates Al-Cr-based intermetallic compounds, which acts on grain coarsening after brazing. Therefore, the aluminum alloy material may contain Cr as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Cr content in the aluminum alloy material is not particularly limited, but if the Cr content in the aluminum alloy material is 0.05 mass% or more, the effect of improving the strength of the aluminum alloy material can be obtained. Therefore, the Cr content in the aluminum alloy material is preferably 0.05 mass% or more with respect to the total mass of the aluminum alloy material, and more preferably 0.10 mass% or more. On the other hand, if the Cr content in the aluminum alloy material exceeds 0.30 mass%, giant intermetallic compounds are likely to be formed, and the plastic workability may be reduced. Therefore, the Cr content in the aluminum alloy material is 0.30 mass% or less, preferably 0.25 mass% or less, and more preferably 0.20 mass% or less with respect to the total mass of the aluminum alloy material.

[0053] (Ti: 0.30% by mass or less) Ti is an element that has the effect of improving the strength of an aluminum alloy material by solid solution strengthening. Therefore, the aluminum alloy material may contain Ti as necessary, but may contain 0 mass%. In this embodiment, the lower limit of the Ti content in the aluminum alloy material is not particularly limited, but when the Ti content in the aluminum alloy material is 0.05 mass% or more, the effect of improving the strength of the aluminum alloy material can be obtained. Therefore, the Ti content in the aluminum alloy material is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, based on the total mass of the aluminum alloy material. On the other hand, when the Ti content in the aluminum alloy material exceeds 0.30 mass%, a giant intermetallic compound is easily formed, and the plastic workability may be reduced. Therefore, the Ti content in the aluminum alloy material is 0.30 mass% or less, preferably 0.25 mass% or less, more preferably 0.20 mass% or less, based on the total mass of the aluminum alloy material.

[0054] (Zr: 0.30% by mass or less) Zr is an element that improves the strength of the aluminum alloy material by solid solution strengthening, and also precipitates an Al-Zr-based intermetallic compound, which acts on the coarsening of crystal grains after brazing. Therefore, the aluminum alloy material may contain Zr as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Zr content in the aluminum alloy material is not particularly limited, but if the Zr content in the aluminum alloy material is 0.05 mass% or more, the effect of improving the strength of the aluminum alloy material can be obtained. Therefore, the Zr content in the aluminum alloy material is preferably 0.05 mass% or more with respect to the total mass of the aluminum alloy material, and more preferably 0.10 mass% or more. On the other hand, if the Zr content in the aluminum alloy material exceeds 0.30 mass%, giant intermetallic compounds are likely to be formed, and the plastic workability may be reduced. Therefore, the Zr content in the aluminum alloy material is 0.30 mass% or less, preferably 0.25 mass% or less, and more preferably 0.20 mass% or less with respect to the total mass of the aluminum alloy material.

[0055] (V: 0.30% by mass or less) V is an element that has the effect of improving the strength of an aluminum alloy material by solid solution strengthening. Therefore, the aluminum alloy material may contain V as necessary, but may be 0 mass%. In this embodiment, the lower limit of the V content in the aluminum alloy material is not particularly limited, but when the V content in the aluminum alloy material is 0.05 mass% or more, the effect of improving the strength of the aluminum alloy material can be obtained. Therefore, the V content in the aluminum alloy material is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, based on the total mass of the aluminum alloy material. On the other hand, when the V content in the aluminum alloy material exceeds 0.30 mass%, a giant intermetallic compound is easily formed, and the plastic workability may be reduced. Therefore, the V content in the aluminum alloy material is 0.30 mass% or less, preferably 0.25 mass% or less, more preferably 0.20 mass% or less, based on the total mass of the aluminum alloy material.

[0056] (Ca: 0.30% by mass or less) Ca is an element effective for improving corrosion resistance because it shows a pH increasing effect by dissolving, and inhibits a pH drop due to a hydrolysis reaction at a local anode where Al dissolution occurs, thereby inhibiting a corrosion reaction. Therefore, the aluminum alloy material may contain Ca as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Ca content in the aluminum alloy material is not particularly limited, but when the Ca content in the aluminum alloy material is 0.01 mass% or more, the effect of improving the corrosion resistance of the aluminum alloy material can be obtained. Therefore, the Ca content in the aluminum alloy material is preferably 0.01 mass% or more with respect to the total mass of the aluminum alloy material, and more preferably 0.05 mass% or more. On the other hand, when the Ca content in the aluminum alloy material exceeds 0.30 mass%, brazing property may be reduced in brazing using a fluoride-based flux. Therefore, the Ca content in the aluminum alloy material is 0.30 mass% or less with respect to the total mass of the aluminum alloy material, preferably 0.25 mass% or less, and more preferably 0.20 mass% or less.

[0057] (Sc: 0.20% by mass or less) Sc is an element that has the effect of improving the strength of the aluminum alloy material by solid solution strengthening. Therefore, the aluminum alloy material may contain Sc as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Sc content in the aluminum alloy material is not particularly limited, but when the Sc content in the aluminum alloy material is 0.01 mass% or more, the effect of improving the strength of the aluminum alloy material can be obtained. Therefore, the Sc content in the aluminum alloy material is preferably 0.01 mass% or more with respect to the total mass of the aluminum alloy material, and more preferably 0.05 mass% or more. On the other hand, when the Sc content in the aluminum alloy material exceeds 0.20 mass%, cracks may easily occur during cold rolling. Therefore, the Sc content in the aluminum alloy material is 0.20 mass% or less, preferably 0.15 mass% or less, and more preferably 0.10 mass% or less with respect to the total mass of the aluminum alloy material.

[0058] (Ni: 0.30% by mass or less) Ni is an element that crystallizes or precipitates in the alloy structure as an intermetallic compound and has the effect of improving strength. Therefore, the aluminum alloy material may contain Ni as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Ni content in the aluminum alloy material is not particularly limited, but when the Ni content in the aluminum alloy material is 0.01 mass% or more, the effect of improving the strength of the aluminum alloy material can be obtained. Therefore, the Ni content in the aluminum alloy material is preferably 0.01 mass% or more with respect to the total mass of the aluminum alloy material, and more preferably 0.05 mass% or more. On the other hand, when the Ni content in the aluminum alloy material exceeds 0.30 mass%, the solidus temperature of the aluminum alloy material decreases, and melting occurs during brazing. Therefore, the Ni content in the aluminum alloy material is 0.30 mass% or less, preferably 0.25 mass% or less, and more preferably 0.20 mass% or less with respect to the total mass of the aluminum alloy material.

[0059] (Mo: 0.30% by mass or less) Mo is an element that has the effect of improving corrosion resistance by dissolving in water to form a molybdate, which acts as an oxygen diffusion barrier to suppress the reduction reaction of oxygen dissolved in water and suppress general corrosion. Therefore, the aluminum alloy material may contain Mo as necessary, but may contain 0 mass%. In this embodiment, the lower limit of the Mo content in the aluminum alloy material is not particularly limited, but if the Mo content in the aluminum alloy material is 0.01 mass% or more, the effect of improving the corrosion resistance of the aluminum alloy material can be obtained. Therefore, the Mo content in the aluminum alloy material is preferably 0.01 mass% or more with respect to the total mass of the aluminum alloy material, and more preferably 0.05 mass% or more. On the other hand, if the Mo content in the aluminum alloy material exceeds 0.30 mass%, the aluminum alloy may be embrittled and the workability may be deteriorated. Therefore, the Mo content in the aluminum alloy material is 0.30 mass% or less with respect to the total mass of the aluminum alloy material, preferably 0.25 mass% or less, and more preferably 0.20 mass% or less.

[0060] (Remainder: Al and inevitable impurities) The balance of the aluminum alloy material produced in this embodiment is Al and unavoidable impurities. Examples of the unavoidable impurities include Na, Sr, etc. The total amount of the unavoidable impurities in the aluminum alloy material is preferably 0.05 mass% or less with respect to the total mass of the aluminum alloy material.

[0061] (Recycling rate R: 20% to 50%) As described above, in this embodiment, the recycle rate is determined based on the Si content in the casting raw material A so as to obtain a target Si content. The recycle rate R is a value expressed as a percentage of the mass of the casting raw material A relative to the total mass of the aluminum alloy material to be manufactured. By setting the recycle rate R to 20% or more, the effect of reducing CO2 emissions resulting from the use of new metal can be sufficiently obtained. Therefore, the recycle rate R is preferably set to 20% or more, more preferably set to 25% or more, and even more preferably set to 30% or more. In addition, by setting the recycle rate R to 50% or less, the Si content in the aluminum alloy material can be controlled within an appropriate range. Therefore, the recycle rate R is preferably set to 50% or less, more preferably set to 45% or less, and even more preferably set to 40% or less.

[0062] Further, the casting raw material B will be briefly described. The casting raw material B is a raw material added to bring each element of the aluminum alloy material to a target content, so that the elements contained in the casting raw material B and their contents are not particularly limited. However, in this embodiment, the recycling rate is determined based on the Si content in the casting raw material A so that the Si content in the aluminum alloy material is within a predetermined range. Therefore, it is preferable that the casting raw material B does not contain Si. In addition, Zn is an element that lowers the solidus temperature, which is the subject of the present invention. For this reason, it is preferable that only the casting raw material A is used as a supply source for Zn, that is, it is preferable that the casting raw material B does not contain Zn.

[0063] Next, a method for manufacturing a clad material according to an embodiment of the present invention will be described in detail.

[0064] [Method of manufacturing clad materials] The method for producing a clad material according to the present embodiment is a method for producing a clad material including an aluminum alloy material produced by the method for producing an aluminum alloy material according to the present embodiment. Specifically, the aluminum alloy material is used as an aluminum alloy material for a core material, and the aluminum alloy material for the core material and at least one or more functional aluminum alloy materials are laminated to produce a clad material.

[0065] The functional aluminum alloy material includes at least one of an aluminum alloy material for brazing material and an aluminum alloy material for sacrificial anode material. The clad material preferably has a structure in which the aluminum alloy material for brazing material / aluminum alloy material for core material / aluminum alloy material for brazing material or aluminum alloy material for sacrificial anode material are laminated in this order. Furthermore, the clad material may include an intermediate layer between the aluminum alloy material for core material and the functional aluminum alloy material.

[0066] The contents of the chemical components in the aluminum alloy material for the brazing material, the aluminum alloy material for the sacrificial anode material and the intermediate layer, as well as the reasons for limiting the numerical values ​​thereof, will be explained below.

[0067] <Aluminum alloys for brazing filler metal> (Si: 2.50 mass% or more and 13.00 mass% or less) The Si in the aluminum alloy material for brazing material improves the liquid phase rate at the brazing heating temperature and ensures the amount of molten brazing material. If the Si content in the aluminum alloy material for brazing material is 2.50 mass% or more, the amount of molten brazing material can be sufficiently ensured, and the fluidity of the molten brazing material can be properly maintained, so that excellent brazing properties can be obtained. Therefore, the Si content in the aluminum alloy material for brazing material is preferably 2.50 mass% or more, more preferably 3.00 mass% or more, and even more preferably 3.50 mass% or more, based on the total mass of the aluminum alloy material for brazing material. In addition, if the Si content in the aluminum alloy material for brazing material is 13.00 mass% or less, the fluidity of the molten brazing material can be prevented from becoming too high, and the occurrence of erosion due to the molten brazing material can be suppressed. Therefore, the Si content in the aluminum alloy material for brazing material is preferably 13.00 mass% or less, more preferably 12.50 mass% or less, and even more preferably 12.00 mass% or less, based on the total mass of the aluminum alloy material for brazing material.

[0068] (Fe: 0.05 mass% or more and 1.00 mass% or less) The Fe in the brazing material aluminum alloy material is likely to form Al-Fe-based or Al-Fe-Si-based compounds, and the formation of the Al-Fe-Si-based compounds reduces the effective Si content of the brazing material. In addition, the formation of the Al-Fe-based or Al-Fe-Si-based compounds may reduce the fluidity of the brazing material during brazing, which may hinder brazing properties. Since Fe is contained in commonly used aluminum alloy materials, if the Fe content in the brazing material aluminum alloy material is 0.05 mass% or more, it is not necessary to use high-purity ingots as a raw material for manufacturing the brazing material aluminum alloy material. Therefore, the Fe content in the brazing material aluminum alloy material is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and even more preferably 0.12 mass% or more, based on the total mass of the brazing material aluminum alloy material. On the other hand, if the Fe content in the brazing material aluminum alloy material is 1.00 mass% or less, good brazing properties can be obtained. Therefore, the Fe content in the aluminum alloy material for brazing filler metal is preferably 1.00 mass% or less, more preferably 0.80 mass% or less, and even more preferably 0.60 mass% or less, based on the total mass of the aluminum alloy material for brazing filler metal.

[0069] (Zn: 5.50% by mass or less) Zn is an alloying element that makes the potential of the aluminum alloy less noble. Therefore, by containing Zn in the aluminum alloy material for brazing material, it can act as a sacrificial anode material and obtain the effect of sacrificial corrosion protection, but in this embodiment, the Zn content in the aluminum alloy material for brazing material may be 0 mass%. In addition, if the Zn content in the aluminum alloy material for brazing material is 5.50 mass% or less, it is possible to prevent the deterioration of workability and suppress the occurrence of cracks during cold rolling. Therefore, the Zn content in the aluminum alloy material for brazing material is preferably 5.50 mass% or less, more preferably 5.00 mass% or less, and even more preferably 4.50 mass% or less with respect to the total mass of the aluminum alloy material for brazing material.

[0070] (Mn: 1.00% by mass or less) Mn in the aluminum alloy material for brazing material has the effect of improving the viscosity of the molten brazing material and suppressing the flow of the molten brazing material, but in this embodiment, the Mn content in the aluminum alloy material for brazing material may be 0 mass%. In addition, if the Mn content in the aluminum alloy material for brazing material is 1.00 mass% or less, it is possible to suppress the generation of Al-Mn(-Fe-Si)-based compounds with a high specific gravity in the molten brazing material, and the amount of molten brazing material can be kept appropriate. Therefore, the Mn content in the aluminum alloy material for brazing material is preferably 1.00 mass% or less, more preferably 0.95 mass% or less, and even more preferably 0.90 mass% or less, based on the total mass of the aluminum alloy material for brazing material.

[0071] (Cu: 1.00% by mass or less) Cu in the brazing material aluminum alloy material has the effect of improving the corrosion resistance of the region formed when brazing heat is applied, but in this embodiment, the Cu content in the brazing material aluminum alloy material may be 0 mass%. In addition, when the Cu content in the brazing material aluminum alloy material is 1.00 mass% or less, diffusion into the intermediate material during brazing heat is suppressed, and the deterioration of corrosion resistance when brazing heat is applied can be prevented. Therefore, the Cu content in the brazing material aluminum alloy material is preferably 1.00 mass% or less, more preferably 0.95 mass% or less, and even more preferably 0.90 mass% or less with respect to the total mass of the brazing material aluminum alloy material.

[0072] (Cr: 0.30 mass% or less) Cr in the brazing material aluminum alloy material improves strength by solid solution strengthening, and also precipitates Al-Cr intermetallic compounds to coarsen crystal grains after brazing, but in this embodiment, the Cr content in the brazing material aluminum alloy material may be 0 mass%. Also, if the Cr content in the brazing material aluminum alloy material is 0.30 mass% or less, the formation of giant intermetallic compounds can be suppressed, and good plastic workability can be obtained. Therefore, the Cr content in the brazing material aluminum alloy material is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the brazing material aluminum alloy material.

[0073] (Ti: 0.30% by mass or less) Ti in the aluminum alloy material for brazing material has the effect of improving the viscosity of the molten brazing material and suppressing the flow of the molten brazing material, but in this embodiment, the Ti content in the aluminum alloy material for brazing material may be 0 mass%. In addition, if the Ti content in the aluminum alloy material for brazing material is 0.30 mass% or less, it is possible to suppress the generation of Al-Ti compounds with a high specific gravity in the molten brazing material, and it is possible to prevent the molten brazing material from flowing downward in the vertical direction from becoming excessive. Therefore, the Ti content in the aluminum alloy material for brazing material is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the aluminum alloy material for brazing material.

[0074] (Zr: 0.30% by mass or less) Zr in the brazing material aluminum alloy material improves strength by solid solution strengthening, and also precipitates Al-Zr-based intermetallic compounds, which acts to coarsen crystal grains after brazing. In this embodiment, the Zr content in the brazing material aluminum alloy material may be 0 mass%. In addition, if the Zr content in the brazing material aluminum alloy material is 0.30 mass% or less, the formation of giant intermetallic compounds can be suppressed, and the deterioration of plastic workability can be prevented. Therefore, the Zr content in the brazing material aluminum alloy material is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the brazing material aluminum alloy material.

[0075] (V: 0.30% by mass or less) V in the aluminum alloy material for brazing filler metal is an element that has the effect of improving strength by solid solution strengthening, but in this embodiment, the V content in the aluminum alloy material for brazing filler metal may be 0 mass%. In addition, when the V content in the aluminum alloy material for brazing filler metal is 0.30 mass% or less, the formation of giant intermetallic compounds can be suppressed, and the deterioration of plastic workability can be prevented. Therefore, the V content in the aluminum alloy material for brazing filler metal is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the aluminum alloy material for brazing filler metal.

[0076] (Ca: 0.30% by mass or less) Ca is an element effective for improving corrosion resistance because it shows a pH increasing effect by dissolving, and inhibits the pH drop due to hydrolysis reaction at the local anode where Al dissolution occurs, thereby inhibiting the corrosion reaction. Therefore, the aluminum alloy material for brazing material may contain Ca as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Ca content in the aluminum alloy material for brazing material is not particularly limited, but when the Ca content in the aluminum alloy material for brazing material is 0.01 mass% or more, the effect of improving the corrosion resistance of the aluminum alloy material for brazing material can be obtained. Therefore, the Ca content in the aluminum alloy material for brazing material is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, based on the total mass of the aluminum alloy material for brazing material. On the other hand, when the Ca content in the aluminum alloy material for brazing material exceeds 0.30 mass%, the brazing property may be reduced in brazing using a fluoride-based flux. Therefore, the Ca content in the aluminum alloy material for brazing filler metal is set to 0.30 mass % or less, preferably 0.25 mass % or less, and more preferably 0.20 mass % or less, based on the total mass of the aluminum alloy material for brazing filler metal.

[0077] (Sc:0.20 mass% or less) Sc is an element that has the effect of improving the strength of the aluminum alloy material for brazing material by solid solution strengthening. Therefore, the aluminum alloy material for brazing material may contain Sc as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Sc content in the aluminum alloy material for brazing material is not particularly limited, but when the Sc content in the aluminum alloy material for brazing material is 0.01 mass% or more, the effect of improving the strength of the aluminum alloy material for brazing material can be obtained. Therefore, the Sc content in the aluminum alloy material for brazing material is preferably 0.01 mass% or more with respect to the total mass of the aluminum alloy material for brazing material, and more preferably 0.05 mass% or more. On the other hand, when the Sc content in the aluminum alloy material for brazing material exceeds 0.20 mass%, cracks may easily occur during cold rolling. Therefore, the Sc content in the aluminum alloy material for brazing material is 0.20 mass% or less, preferably 0.15 mass% or less, and more preferably 0.10 mass% or less with respect to the total mass of the aluminum alloy material for brazing material.

[0078] (Ni: 0.30% by mass or less) Ni is an element that crystallizes or precipitates in the alloy structure as an intermetallic compound and has the effect of improving strength. Therefore, the aluminum alloy material for brazing material may contain Ni as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Ni content in the aluminum alloy material for brazing material is not particularly limited, but when the Ni content in the aluminum alloy material for brazing material is 0.01 mass% or more, the effect of improving the strength of the aluminum alloy material for brazing material can be obtained. Therefore, the Ni content in the aluminum alloy material for brazing material is preferably 0.01 mass% or more with respect to the total mass of the aluminum alloy material, and more preferably 0.05 mass% or more. On the other hand, when the Ni content in the aluminum alloy material for brazing material exceeds 0.30 mass%, the solidus temperature of the aluminum alloy material for brazing material decreases. Therefore, the Ni content in the aluminum alloy material for brazing material is 0.30 mass% or less, preferably 0.25 mass% or less, and more preferably 0.20 mass% or less with respect to the total mass of the aluminum alloy material for brazing material.

[0079] (Mo: 0.30% by mass or less) Mo is an element that has the effect of improving corrosion resistance by dissolving in water to form a molybdate, which acts as an oxygen diffusion barrier to suppress the reduction reaction of oxygen dissolved in water and suppress general corrosion. Therefore, the aluminum alloy material for brazing material may contain Mo as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Mo content in the aluminum alloy material for brazing material is not particularly limited, but when the Mo content in the aluminum alloy material for brazing material is 0.01 mass% or more, the effect of improving the corrosion resistance of the aluminum alloy material for brazing material can be obtained. Therefore, the Mo content in the aluminum alloy material for brazing material is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, based on the total mass of the aluminum alloy material for brazing material. On the other hand, when the Mo content in the aluminum alloy material for brazing material exceeds 0.30 mass%, the aluminum alloy material for brazing material may be embrittled and the workability may be deteriorated. Therefore, the Mo content in the aluminum alloy material for brazing filler metal is set to 0.30 mass % or less, preferably 0.25 mass % or less, and more preferably 0.20 mass % or less, based on the total mass of the aluminum alloy material for brazing filler metal.

[0080] (Sb: 0.30% by mass or less) Sb in the aluminum alloy material for brazing filler metal is an element that has the effect of refining Si particles and improving brazing properties, but in this embodiment, the Sb content in the aluminum alloy material for brazing filler metal may be 0 mass%. In addition, if the Sb content in the aluminum alloy material for brazing filler metal is 0.30 mass% or less, the fluidity of the brazing filler metal can be prevented from decreasing. Therefore, the Sb content in the aluminum alloy material for brazing filler metal is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the aluminum alloy material for brazing filler metal.

[0081] (Sr: 0.10% by mass or less) Sr in the aluminum alloy material for brazing filler metal is an element that has the effect of refining Si particles and improving brazing properties, but in this embodiment, the Sr content in the aluminum alloy material for brazing filler metal may be 0 mass%. In addition, if the Sr content in the aluminum alloy material for brazing filler metal is 0.10 mass% or less, oxidation of Sr during casting can be prevented. Therefore, the Sr content in the aluminum alloy material for brazing filler metal is preferably 0.10 mass% or less, more preferably 0.05 mass% or less, and even more preferably 0.02 mass% or less, based on the total mass of the aluminum alloy material for brazing filler metal.

[0082] (Na: 0.10% by mass or less) Na in the aluminum alloy material for brazing filler metal is an element that has the effect of refining Si particles and improving brazing properties, but in this embodiment, the Na content in the aluminum alloy material for brazing filler metal may be 0 mass%. In addition, if the Na content in the aluminum alloy material for brazing filler metal is 0.10 mass% or less, oxidation of Na during casting can be prevented. Therefore, the Na content in the aluminum alloy material for brazing filler metal is preferably 0.10 mass% or less, more preferably 0.05 mass% or less, and even more preferably 0.02 mass% or less, based on the total mass of the aluminum alloy material for brazing filler metal.

[0083] (Remainder: Al and inevitable impurities) The balance of the aluminum alloy material for brazing filler metal in the clad material is Al and inevitable impurities. The inevitable impurities include rare earth elements other than Be and Sc, Li, etc. In detail, Be may be contained in a range of 0.01 mass% or less, and other elements may be contained in a range of less than 0.01 mass%. In addition, the total amount of inevitable impurities in the aluminum alloy material for brazing filler metal is preferably 0.05 mass% or less with respect to the total mass of the aluminum alloy material for brazing filler metal.

[0084] <Aluminum alloy for sacrificial anodes> (Zn: 0.50 mass% or more and 6.00 mass% or less) Zn in the aluminum alloy material for sacrificial anode material is an element that has the effect of preventing pitting corrosion and crevice corrosion by making the potential of the base material lower and enhancing the sacrificial corrosion protection effect for the aluminum alloy material for core material and the intermediate layer. If the Zn content in the aluminum alloy material for sacrificial anode material is 0.50 mass% or more, a sufficient sacrificial corrosion protection effect can be obtained. Therefore, the Zn content in the aluminum alloy material for sacrificial anode material is preferably 0.50 mass% or more, more preferably 0.60 mass% or more, and even more preferably 0.70 mass% or more, based on the total mass of the aluminum alloy material for sacrificial anode material. In addition, if the Zn content in the aluminum alloy material for sacrificial anode material is 6.00 mass% or less, the self-corrosion of the sacrificial anode material can be prevented from increasing too much, and the corrosion resistance of the clad material can be suppressed from decreasing. Therefore, the Zn content in the aluminum alloy material for sacrificial anode material is preferably 6.00 mass% or less, more preferably 5.70 mass% or less, and even more preferably 5.50 mass% or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0085] (Si: 0.05 mass% or more and 1.50 mass% or less) Si in the aluminum alloy material for sacrificial anode material is an element that has the effect of improving the strength of the aluminum alloy material for sacrificial anode material. If the Si content in the aluminum alloy material for sacrificial anode material is 0.05 mass% or more, the effect of improving the strength can be obtained. Therefore, the Si content in the aluminum alloy material for sacrificial anode material is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and even more preferably 0.15 mass% or more, based on the total mass of the aluminum alloy material for sacrificial anode material. In addition, if the Si content in the aluminum alloy material for sacrificial anode material is 1.50 mass% or less, the decrease in solidus temperature can be suppressed, and melting during brazing can be prevented. Therefore, the Si content in the aluminum alloy material for sacrificial anode material is preferably 1.50 mass% or less, more preferably 1.45 mass% or less, and even more preferably 1.40 mass% or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0086] (Fe: 0.05% by mass or more and 2.00% by mass or less), Fe in the aluminum alloy material for sacrificial anode material is an element that forms an Al-Fe-Mn-Si compound together with Si and Mn, and has the effect of improving strength by dispersion strengthening. If the Fe content in the aluminum alloy material for sacrificial anode material is 0.05 mass% or more, the effect of improving strength can be obtained. Therefore, the Fe content in the aluminum alloy material for sacrificial anode material is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and even more preferably 0.12 mass% or more, based on the total mass of the aluminum alloy material for sacrificial anode material. In addition, if the Fe content in the aluminum alloy material for sacrificial anode material is 2.00 mass% or less, it is possible to prevent the formation of a giant intermetallic compound during casting, and the deterioration of plastic workability can be suppressed. Therefore, the Fe content in the aluminum alloy material for sacrificial anode material is preferably 2.00 mass% or less, more preferably 1.80 mass% or less, and even more preferably 1.60 mass% or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0087] (Mg: 3.00% by mass or less) Mg in the aluminum alloy material for sacrificial anode material is an element that not only improves the strength of the aluminum alloy material for sacrificial anode material itself by precipitating Mg2Si, but also has the effect of diffusing Mg into the core material by brazing heating to improve the strength of the core material. However, in this embodiment, the Mg content in the aluminum alloy material for sacrificial anode material may be 0 mass%. In addition, if the Mg content in the aluminum alloy material for sacrificial anode material is 3.00 mass% or less, it can be easily pressure-bonded during hot clad rolling. Therefore, the Mg content in the aluminum alloy material for sacrificial anode material is preferably 3.00 mass% or less, more preferably 2.80 mass% or less, and even more preferably 2.60 mass% or less with respect to the total mass of the aluminum alloy material for sacrificial anode material.

[0088] (Mn: 1.80% by mass or less) Mn in the aluminum alloy material for sacrificial anode material is an element that has the effect of improving the strength after brazing by dissolving in the base material or forming an Al-Mn-Si intermetallic compound together with Si. However, in this embodiment, the Mn content in the aluminum alloy material for sacrificial anode material may be 0 mass%. In addition, when the Mn content in the aluminum alloy material for sacrificial anode material is 1.80 mass% or less, the fluidity of the molten brazing material on the surface of the aluminum alloy material for sacrificial anode material side during brazing is increased, and brazing properties can be improved. Therefore, the Mn content in the aluminum alloy material for sacrificial anode material is preferably 1.80 mass% or less, more preferably 1.60 mass% or less, and even more preferably 1.40 mass% or less with respect to the total mass of the aluminum alloy material for sacrificial anode material.

[0089] (Cu: 0.50% by mass or less) When the Cu content in the aluminum alloy material for sacrificial anode material is 0.50 mass% or less, the pitting potential of the sacrificial anode material is prevented from becoming noble, and the effect of sacrificial corrosion protection can be sufficiently obtained. Therefore, the Cu content in the aluminum alloy material for sacrificial anode material is preferably 0.50 mass% or less, more preferably 0.40 mass% or less, and even more preferably 0.30 mass% or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0090] (Cr: 0.30 mass% or less) Cr in the aluminum alloy material for sacrificial anode material is an element that has the effect of improving strength by solid solution strengthening, but in this embodiment, the Cr content in the aluminum alloy material for sacrificial anode material may be 0 mass%. In addition, if the Cr content in the aluminum alloy material for sacrificial anode material is 0.30 mass% or less, it is possible to prevent the formation of giant intermetallic compounds during casting, and to suppress the deterioration of plastic workability. Therefore, the Cr content in the aluminum alloy material for sacrificial anode material is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0091] (Ti: 0.30% by mass or less) Ti in the aluminum alloy material for sacrificial anode material is an element that has the effect of improving strength by solid solution strengthening, but in this embodiment, the Ti content in the aluminum alloy material for sacrificial anode material may be 0 mass%. In addition, if the Ti content in the aluminum alloy material for sacrificial anode material is 0.30 mass% or less, it is possible to prevent the formation of giant intermetallic compounds during casting, and to suppress the deterioration of plastic workability. Therefore, the Ti content in the aluminum alloy material for sacrificial anode material is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0092] (Zr: 0.30% by mass or less) Zr in the aluminum alloy material for sacrificial anode material is an element that has the effect of improving strength by solid solution strengthening, but in this embodiment, the Zr content in the aluminum alloy material for sacrificial anode material may be 0 mass%. In addition, if the Zr content in the aluminum alloy material for sacrificial anode material is 0.30 mass% or less, it is possible to prevent the formation of giant intermetallic compounds during casting, and to suppress the deterioration of plastic workability. Therefore, the Zr content in the aluminum alloy material for sacrificial anode material is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0093] (V: 0.30% by mass or less) V in the aluminum alloy material for sacrificial anode material is an element that has the effect of improving strength by solid solution strengthening, but in this embodiment, the V content in the aluminum alloy material for sacrificial anode material may be 0 mass%. In addition, if the V content in the aluminum alloy material for sacrificial anode material is 0.30 mass% or less, it is possible to prevent the formation of giant intermetallic compounds during casting, and to suppress the deterioration of plastic workability. Therefore, the V content in the aluminum alloy material for sacrificial anode material is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0094] (Ca: 0.30% by mass or less) Ca is an element effective for improving corrosion resistance because it shows a pH increasing effect by dissolving, and suppresses the pH drop due to the hydrolysis reaction at the local anode where Al dissolution occurs, thereby suppressing the corrosion reaction. Therefore, the aluminum alloy material for sacrificial anode material may contain Ca as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Ca content in the aluminum alloy material for sacrificial anode material is not particularly limited, but when the Ca content in the aluminum alloy material for sacrificial anode material is 0.01 mass% or more, the effect of improving the corrosion resistance of the aluminum alloy material for sacrificial anode material can be obtained. Therefore, the Ca content in the aluminum alloy material for sacrificial anode material is preferably 0.01 mass% or more with respect to the total mass of the aluminum alloy material for sacrificial anode material, and more preferably 0.05 mass% or more. On the other hand, when the Ca content in the aluminum alloy material for sacrificial anode material exceeds 0.30 mass%, the brazing property may be reduced in brazing using a fluoride-based flux. Therefore, the Ca content in the aluminum alloy material for sacrificial anode material is 0.30 mass % or less, preferably 0.25 mass % or less, and more preferably 0.20 mass % or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0095] (Sc: 0.20% by mass or less) Sc is an element that has the effect of improving the strength of the aluminum alloy material for sacrificial anode material by solid solution strengthening. Therefore, the aluminum alloy material for sacrificial anode material may contain Sc as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Sc content in the aluminum alloy material for sacrificial anode material is not particularly limited, but when the Sc content in the aluminum alloy material for sacrificial anode material is 0.01 mass% or more, the effect of improving the strength of the aluminum alloy material for sacrificial anode material can be obtained. Therefore, the Sc content in the aluminum alloy material for sacrificial anode material is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, based on the total mass of the aluminum alloy material for sacrificial anode material. On the other hand, when the Sc content in the aluminum alloy material for sacrificial anode material exceeds 0.20 mass%, cracks may easily occur during cold rolling. Therefore, the Sc content in the aluminum alloy material for sacrificial anode material is 0.20 mass % or less, preferably 0.15 mass % or less, and more preferably 0.10 mass % or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0096] (Ni: 0.30% by mass or less) Ni is an element that crystallizes or precipitates in the alloy structure as an intermetallic compound and has the effect of improving strength. Therefore, the aluminum alloy material for sacrificial anode material may contain Ni as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Ni content in the aluminum alloy material for sacrificial anode material is not particularly limited, but if the Ni content in the aluminum alloy material for sacrificial anode material is 0.01 mass% or more, the effect of improving the strength of the aluminum alloy material for sacrificial anode material can be obtained. Therefore, the Ni content in the aluminum alloy material for sacrificial anode material is preferably 0.01 mass% or more with respect to the total mass of the aluminum alloy material, and more preferably 0.05 mass% or more. On the other hand, if the Ni content in the aluminum alloy material for sacrificial anode material exceeds 0.30 mass%, the solidus temperature of the aluminum alloy material for sacrificial anode material decreases. Therefore, the Ni content in the aluminum alloy material for sacrificial anode material is 0.30 mass % or less, preferably 0.25 mass % or less, and more preferably 0.20 mass % or less, based on the total mass of the aluminum alloy material for sacrificial anode material.

[0097] (Mo: 0.30% by mass or less) Mo is an element that has the effect of improving corrosion resistance by dissolving in water to form a molybdate, which acts as an oxygen diffusion barrier to suppress the reduction reaction of oxygen dissolved in water and suppress general corrosion. Therefore, the aluminum alloy material for sacrificial anode material may contain Mo as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Mo content in the aluminum alloy material for sacrificial anode material is not particularly limited, but if the Mo content in the aluminum alloy material for sacrificial anode material is 0.01 mass% or more, the effect of improving the corrosion resistance of the aluminum alloy material for sacrificial anode material can be obtained. Therefore, the Mo content in the aluminum alloy material for sacrificial anode material is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, based on the total mass of the aluminum alloy material for sacrificial anode material. On the other hand, if the Mo content in the aluminum alloy material for sacrificial anode material exceeds 0.30 mass%, the aluminum alloy for sacrificial anode material may be embrittled and the workability may be deteriorated. Therefore, the Mo content in the aluminum alloy material for a sacrificial anode material is 0.30 mass % or less, preferably 0.25 mass % or less, and more preferably 0.20 mass % or less, based on the total mass of the aluminum alloy material for a sacrificial anode material.

[0098] (Remainder: Al and inevitable impurities) The balance of the aluminum alloy material for sacrificial anode material in the clad material is Al and inevitable impurities. The inevitable impurities include rare earth elements other than Be, Sb, and Sc, Li, etc. In detail, Be may be contained in a range of 0.01 mass% or less, and other elements may be contained in a range of less than 0.01 mass%. In addition, the total amount of inevitable impurities in the aluminum alloy material for sacrificial anode material is preferably 0.05 mass% or less with respect to the total mass of the aluminum alloy material for sacrificial anode material.

[0099] <Middle Class> (Si: 0.05 mass% or more and 1.50 mass% or less) Si in the intermediate layer is an element that has the effect of improving the strength after brazing by dissolving in the base material and forming an Al-Mn-Si intermetallic compound together with Mn. When the Si content in the intermediate layer is 0.05 mass% or more, the effect of improving the strength can be sufficiently obtained. Therefore, the Si content in the intermediate layer is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and even more preferably 0.15 mass% or more, based on the total mass of the intermediate layer. In addition, when the Si content in the intermediate layer is 1.50 mass% or less, the decrease in the solidus temperature can be suppressed, and melting during brazing can be prevented. Therefore, the Si content in the intermediate layer is preferably 1.50 mass% or less, more preferably 1.40 mass% or less, and even more preferably 1.30 mass% or less, based on the total mass of the intermediate layer.

[0100] (Fe: 0.05 mass% or more and 2.00 mass% or less) Fe in the intermediate layer is an element that forms an Al-Fe-Mn-Si compound together with Si and Mn, and has the effect of improving strength by dispersion strengthening. When the Fe content in the intermediate layer is 0.05 mass% or more, the effect of improving strength can be sufficiently obtained. Therefore, the Fe content in the intermediate layer is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and even more preferably 0.12 mass% or more, based on the total mass of the intermediate layer. In addition, when the Fe content in the intermediate layer is 2.00 mass% or less, it is possible to prevent the formation of giant intermetallic compounds during casting, and it is possible to suppress the deterioration of plastic workability. Therefore, the Fe content in the intermediate layer is preferably 2.00 mass% or less, more preferably 1.80 mass% or less, and even more preferably 1.60 mass% or less, based on the total mass of the intermediate layer.

[0101] (Zn: 6.00% by mass or less) Zn in the intermediate layer is an element that has the effect of lowering the potential of the intermediate layer and improving the corrosion resistance, but in this embodiment, the Zn content in the intermediate layer may be 0 mass%. In addition, if the Zn content in the intermediate layer is 6.00 mass% or less, the solidus temperature of the intermediate layer can be suppressed from decreasing, and the intermediate layer can be prevented from melting during brazing. Therefore, the Zn content in the intermediate layer is preferably 6.00 mass% or less, more preferably 5.80 mass% or less, and even more preferably 5.60 mass% or less, based on the total mass of the intermediate layer.

[0102] (Mn: 1.80% by mass or less) Mn in the intermediate layer is an element that has the effect of improving the strength after brazing by dissolving in the base material and forming an Al-Mn-Si intermetallic compound together with Si. However, in this embodiment, the Mn content in the intermediate layer may be 0 mass%. Furthermore, if the Mn content in the intermediate layer is 1.80 mass% or less, it is possible to prevent the precipitation of coarse intermetallic compounds and suppress the deterioration of rollability. Therefore, the Mn content in the intermediate layer is preferably 1.80 mass% or less, more preferably 1.70 mass% or less, and even more preferably 1.60 mass% or less, based on the total mass of the intermediate layer.

[0103] (Cu: 1.00% by mass or less) Cu in the intermediate layer is an element that dissolves in the base material after brazing and has the effect of improving the strength after brazing. However, in this embodiment, the Cu content in the intermediate layer may be 0 mass%. Furthermore, when the Cu content in the intermediate layer is 1.00 mass% or less, the decrease in the solidus temperature can be suppressed and the intermediate layer can be prevented from melting during brazing. Therefore, the Cu content in the intermediate layer is preferably 1.00 mass% or less, more preferably 0.90 mass% or less, and even more preferably 0.80 mass% or less, based on the total mass of the intermediate layer.

[0104] (Cr: 0.30 mass% or less) Cr in the intermediate layer is an element that has the effect of improving strength by solid solution strengthening, but in this embodiment, the Cr content in the intermediate layer may be 0 mass%. Furthermore, if the Cr content in the intermediate layer is 0.30 mass% or less, it is possible to prevent the formation of giant intermetallic compounds during casting, and to suppress the deterioration of plastic workability. Therefore, the Cr content in the intermediate layer is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the intermediate layer.

[0105] (Ti: 0.30% by mass or less) Ti in the intermediate layer is an element that has the effect of improving strength by solid solution strengthening, but in this embodiment, the Ti content in the intermediate layer may be 0 mass%. Furthermore, if the Ti content in the intermediate layer is 0.30 mass% or less, it is possible to prevent the formation of giant intermetallic compounds during casting, and to suppress the deterioration of plastic workability. Therefore, the Ti content in the intermediate layer is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the intermediate layer.

[0106] (Zr: 0.30% by mass or less) Zr in the intermediate layer is an element that has the effect of improving strength by solid solution strengthening, but in this embodiment, the Zr content in the intermediate layer may be 0 mass%. Furthermore, if the Zr content in the intermediate layer is 0.30 mass% or less, it is possible to prevent the formation of giant intermetallic compounds during casting, and to suppress the deterioration of plastic workability. Therefore, the Zr content in the intermediate layer is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the intermediate layer.

[0107] (V: 0.30% by mass or less) V in the intermediate layer is an element that has the effect of improving strength by solid solution strengthening, but in this embodiment, the V content in the intermediate layer may be 0 mass%. Furthermore, if the V content in the intermediate layer is 0.30 mass% or less, it is possible to prevent the formation of giant intermetallic compounds during casting, and to suppress the deterioration of plastic workability. Therefore, the V content in the intermediate layer is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and even more preferably 0.10 mass% or less, based on the total mass of the intermediate layer.

[0108] (Ca: 0.30% by mass or less) Ca is an element effective for improving corrosion resistance because it shows a pH increasing effect by dissolving, and inhibits a pH drop due to a hydrolysis reaction at a local anode where Al dissolution occurs, thereby inhibiting a corrosion reaction. Therefore, the intermediate layer may contain Ca as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Ca content in the intermediate layer is not particularly limited, but when the Ca content in the intermediate layer is 0.01 mass% or more, the effect of improving the corrosion resistance of the intermediate layer can be obtained. Therefore, the Ca content in the intermediate layer is preferably 0.01 mass% or more with respect to the total mass of the intermediate layer, and more preferably 0.05 mass% or more. On the other hand, when the Ca content in the intermediate layer exceeds 0.30 mass%, brazing properties may be reduced in brazing using a fluoride-based flux. Therefore, the Ca content in the intermediate layer is 0.30 mass% or less with respect to the total mass of the intermediate layer, preferably 0.25 mass% or less, and more preferably 0.20 mass% or less.

[0109] (Sc:0.20 mass% or less) Sc is an element that has the effect of improving the strength of the intermediate layer by solid solution strengthening. Therefore, the intermediate layer may contain Sc as necessary, but may be 0 mass%. In this embodiment, the lower limit of the Sc content in the intermediate layer is not particularly limited, but when the Sc content in the intermediate layer is 0.01 mass% or more, the effect of improving the strength of the intermediate layer can be obtained. Therefore, the Sc content in the intermediate layer is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, based on the total mass of the intermediate layer. On the other hand, when the Sc content in the intermediate layer exceeds 0.20 mass%, cracks may easily occur during cold rolling. Therefore, the Sc content in the intermediate layer is 0.20 mass% or less, preferably 0.15 mass% or less, more preferably 0.10 mass% or less, based on the total mass of the intermediate layer.

[0110] (Ni: 0.30% by mass or less) Ni is an element that crystallizes or precipitates in the alloy structure as an intermetallic compound and has the effect of improving strength. Therefore, the intermediate layer may contain Ni as necessary, but may contain 0 mass%. In this embodiment, the lower limit of the Ni content in the intermediate layer is not particularly limited, but if the Ni content in the intermediate layer is 0.01 mass% or more, the effect of improving the strength of the intermediate layer can be obtained. Therefore, the Ni content in the intermediate layer is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, based on the total mass of the aluminum alloy material. On the other hand, if the Ni content in the intermediate layer exceeds 0.30 mass%, the solidus temperature of the intermediate layer decreases. Therefore, the Ni content in the intermediate layer is 0.30 mass% or less, preferably 0.25 mass% or less, more preferably 0.20 mass% or less, based on the total mass of the intermediate layer.

[0111] (Mo: 0.30% by mass or less) Mo is an element that has the effect of improving corrosion resistance by dissolving in water to form a molybdate, which acts as an oxygen diffusion barrier to suppress the reduction reaction of oxygen dissolved in water and suppress general corrosion. Therefore, the intermediate layer may contain Mo as necessary, but may contain 0 mass%. In this embodiment, the lower limit of the Mo content in the intermediate layer is not particularly limited, but if the Mo content in the intermediate layer is 0.01 mass% or more, the effect of improving the corrosion resistance of the intermediate layer can be obtained. Therefore, the Mo content in the intermediate layer is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, based on the total mass of the intermediate layer. On the other hand, if the Mo content in the intermediate layer exceeds 0.30 mass%, the intermediate layer may be embrittled and the workability may be deteriorated. Therefore, the Mo content in the intermediate layer is 0.30 mass% or less, preferably 0.25 mass% or less, more preferably 0.20 mass% or less, based on the total mass of the intermediate layer.

[0112] (Remainder: Al and inevitable impurities) The remainder of the intermediate layer in the clad material is Al and unavoidable impurities. Examples of unavoidable impurities include rare earth elements other than Be, Sb, and Sc, and Li. In detail, Be may be contained in a range of 0.01 mass% or less, and other elements may be contained in a range of less than 0.01 mass%. In addition, the total amount of unavoidable impurities in the intermediate layer is preferably 0.05 mass% or less with respect to the total mass of the intermediate layer. EXAMPLES

[0113] The present embodiment will be described in more detail below with reference to examples. However, the present invention is not limited to these examples, and modifications can be made within the scope of the invention, and all such modifications are included in the technical scope of the invention.

[0114] <Production of aluminum alloy materials> Aluminum alloy materials having various chemical compositions were manufactured by assuming that scrap (casting raw material A) having various chemical compositions shown in Table 1 below and additive casting raw material B having various chemical compositions shown in Table 2 below were used. The content of each component of the aluminum alloy materials and the recycling rate are shown in Table 3.

[0115] <Clad material production> After casting ingots having various compositions, homogenization treatment was performed, each surface was cut, and further hot rolling was performed to obtain a desired plate thickness, to produce functional aluminum alloy materials (aluminum alloy materials for brazing material and aluminum alloy materials for sacrificial anode material) having the composition shown in Table 4 below. Then, a part of the aluminum alloy material shown in Table 3 was used as a core material, and functional aluminum alloy materials were laminated on only one surface or both one surface and the other surface, hot rolling was performed, and then heating and hot rolling were performed again. Then, in the case of O and H24 tempers, cold rolling and final annealing were performed to produce test materials (Nos. T1 to T5 and T21) with a predetermined final plate thickness. In addition, in the case of H14 temper, cold rolling, intermediate annealing, and cold rolling were performed to produce test materials (Nos. T6 to T7, T9) with a predetermined final plate thickness. In the case of H34 temper, cold rolling, intermediate annealing, cold rolling, and stabilization treatment were performed to produce test material (No. T8) with the specified final plate thickness. The aluminum alloy material No. used for evaluation, and the clad material produced are shown in Table 5 below, along with the functional aluminum alloy material No. used, clad ratio, temper type, and final plate thickness of the clad material.

[0116] In Tables 1 to 4, in the column of the content of each component, "-" indicates that the element is not contained or that the content is less than 0.05 mass%. The balance of each component in the aluminum alloy material and the functional aluminum alloy material shown in Tables 3 and 4 is Al and unavoidable impurities.

[0117] <Evaluation of test materials> (Calculation of solidus temperature) The solidus temperature of the obtained aluminum alloy material was calculated by integrated thermodynamic calculation software (Thermo-Calc). The temperature at which the liquid phase ratio exceeded 1% in the calculation was defined as the "solidus temperature of the aluminum alloy material."

[0118] (Measurement of tensile strength) A tensile test was carried out on the obtained clad material in accordance with JIS Z 2241 to measure the tensile strength.

[0119] (Flow coefficient) The flow coefficients of test material No. T9, in which the Mg content of the aluminum alloy material was 0.01 mass%, and test material No. T21, in which the Mg content of the aluminum alloy material was 0.17 mass%, were calculated by an inverted T-shaped flow test. The flow test was performed by applying aluminum brazing flux FL-7 (manufactured by Morita Chemical Industries Co., Ltd.) at a rate of 5±0.1 g / m to the brazing material surface of the aluminum alloy material. 2 The test was carried out by applying the coating amount of 100% tin to the aluminum alloy material, assembling the material into an inverted T-shape, and then brazing the material. The brazing conditions in the test were 600°C x 3 minutes. Since the Mg content affects the flow coefficient, the flow coefficients of the test materials other than test material No. T9 and T21 were not measured because the aluminum alloy material does not contain Mg and it is assumed that the flow coefficient is 0.57 or more. The measurement results are also shown in Table 5 below.

[0120] In the clad material column in Table 5, "-" indicates that the clad material was not produced. In the measurement results, "-" indicates that the measurement was not performed. In addition, in the evaluation results column in Table 5, those with a solidus temperature of 600°C or higher and a flow coefficient of 0.40 or higher were judged to have excellent brazability and were marked with "○". Those that did not meet the above criteria in either one were judged to have poor brazability and were marked with "×". As described above, the magnesium content in the aluminum alloy material of test material Nos. T1 to T8, T10 to T20, and T22 to T25 is less than that of test material No. T9, so that the flow coefficient can be judged to be 0.57 or more.

[0121] [Table 1]

[0122] [Table 2]

[0123] [Table 3]

[0124] [Table 4]

[0125] [Table 5]

[0126] As shown in Tables 1 to 5 above, in the test materials No. T1 to T20 of the invention, aluminum alloy scrap material with a Mg content of 0.10 mass% or less was used as the casting raw material A. In addition, the recycling rate was determined based on the Si content in the casting raw material A, and aluminum alloy materials were manufactured so as to have a predetermined solidus temperature, and some of them were made into clad materials. Therefore, the brazing property was evaluated as being good. In this way, when the aluminum alloy material was manufactured by the manufacturing method according to the present invention, scraps of automobile heat exchangers in which clad materials are used and aluminum alloy clad materials used in automobile heat exchangers could be reused. In addition, even when the recycling rate was 20% or more, it was possible to manufacture aluminum alloy materials with excellent brazing property, so that the amount of new ingots used could be reduced, and CO2 emissions could be significantly reduced.

[0127] On the other hand, in the comparative example, test material No. T21, the casting raw material A containing more than 0.10 mass% Mg was used, and the Mg content in the aluminum alloy material exceeded the upper limit specified in the present invention, resulting in poor brazability. In the test material No. T22, the Mn content in the aluminum alloy material was below the lower limit specified in the present invention, and therefore the brazeability was poor. For test materials No. T23 and T24, the Si content in the casting raw material A is expressed as [Si] A , the formula (1): [Si] A × R / 100 exceeded 1.10. A was 2.20, and the recycle rates of test materials No. T23 and T24 were 55% and 54%, respectively, so the values ​​calculated by formula (1) were 1.20 and 1.19, respectively. Therefore, the Si content in the aluminum alloy material exceeded the upper limit specified in the present invention, and the brazeability was poor. In the test No. T25, the Zn content in the aluminum alloy material exceeded the upper limit specified in the present invention, and therefore the brazeability was poor. In the test No. T26, the Cu content in the aluminum alloy material exceeded the upper limit specified in the present invention, and therefore the brazeability was poor.

Claims

1. A method for producing an aluminum alloy material, comprising the steps of: producing an aluminum alloy material using a casting raw material A and a casting raw material B; a selection step of selecting only aluminum alloy scrap material having a Mg content of 0.10 mass% or less from at least one of scrap of automotive heat exchangers using clad materials and scrap of aluminum alloy clad materials used for automotive heat exchangers, as the casting raw material A; A casting process for casting an ingot using the casting raw material A and the casting raw material B for addition; A molding process of molding the ingot into an aluminum alloy material having a solidus temperature of 600° C. or more, The recycling rate representing the mass ratio of the casting raw material A to the total mass of the ingot is R (%), and the Si content in the casting raw material A is [Si] in mass%. A , when expressing Between the selection step and the casting step, Expression (1): [Si] A ×R / 100 The value calculated by is 0.50 or more and 1.10 or less, A recycle rate determination step of determining a recycle rate R such that The casting step is a step of casting the ingot using the casting raw material A, which is R (%) with respect to a total mass of the ingot, and the casting raw material B, which is (100-R) (%) with respect to a total mass of the ingot, The casting raw material A is, with respect to the total mass of the casting raw material A, Si: 0.50 mass% or more, and Zn: 0.10% by mass or more, Contains at least one element selected from Fe: 0.10% by mass or more, Cu: 0.08% by mass or more, and Mn: 0.50% by mass or more; The aluminum alloy material is Si: 0.50% by mass or more and 1.10% by mass or less, Fe: 0.10% by mass or more and 1.00% by mass or less, Cu: 0.08% by mass or more and 0.80% by mass or less, Mn: 0.90% by mass or more and 1.80% by mass or less, and Zn: 0.10% by mass or more and 1.00% by mass or less; Mg: 0.10% by mass or less, Ti: 0.30% by mass or less, Cr: 0.30% by mass or less, Zr: 0.30% by mass or less, V: 0.30% by mass or less, Ca: 0.30% by mass or less, Sc: 0.20% by mass or less, Ni: 0.30% by mass or less, 1. A method for producing an aluminum alloy material, comprising: Mo: 0.30 mass% or less; and the balance consisting of Al and unavoidable impurities.

2. The method for producing an aluminum alloy material according to claim 1, wherein the recycling rate R is 20% or more and 50% or less.

3. The method for producing an aluminum alloy material according to claim 1, wherein the casting raw material B does not contain Si.

4. The method for producing an aluminum alloy material according to claim 1, wherein the casting raw material B does not contain Zn.

5. 2. The method for producing an aluminum alloy material according to claim 1, wherein the casting raw material A contains Zn: 1.00 mass % or less.

6. A method for producing a clad material comprising an aluminum alloy material produced by the method according to any one of claims 1 to 5, The aluminum alloy material is used as a core aluminum alloy material, A method for producing a clad material, comprising laminating the aluminum alloy material for a core material and at least one type of functional aluminum alloy material to produce a clad material.

7. 7. The method for producing a clad material according to claim 6, wherein the functional aluminum alloy material includes at least one of an aluminum alloy material for brazing material and an aluminum alloy material for sacrificial anode material.

8. The aluminum alloy material for brazing filler metal is Si: 2.50% by mass or more and 13.00% by mass or less, and Fe: 0.05% by mass or more and 1.00% by mass or less; Zn: 5.50% by mass or less, Mn: 1.00% by mass or less, Cu: 1.00% by mass or less, Cr: 0.30% by mass or less, Ti: 0.30% by mass or less, Zr: 0.30% by mass or less, V: 0.30% by mass or less, Ca: 0.30% by mass or less, Sc: 0.20% by mass or less, Ni: 0.30% by mass or less, Mo: 0.30% by mass or less, Sb: 0.30% by mass or less, Sr: 0.10% by mass or less, The method for producing a clad material according to claim 7, characterized in that Na is 0.10 mass % or less, with the balance being Al and unavoidable impurities.

9. The aluminum alloy material for the sacrificial anode material is Zn: 0.50% by mass or more and 6.00% by mass or less, Si: 0.05% by mass or more and 1.50% by mass or less, and Fe: 0.05% by mass or more and 2.00% by mass or less; Mg: 3.00% by mass or less, Mn: 1.80% by mass or less, Cu: 0.50% by mass or less, Cr: 0.30% by mass or less, Ti: 0.30% by mass or less, Zr: 0.30% by mass or less, V: 0.30% by mass or less, Ca: 0.30% by mass or less, Sc: 0.20% by mass or less, Ni: 0.30% by mass or less, The method for producing a clad material according to claim 7, characterized in that Mo is 0.30 mass% or less, with the balance being Al and unavoidable impurities.

10. 8. The method for manufacturing a clad material according to claim 7, characterized in that the clad material has a structure in which the aluminum alloy material for brazing material / the aluminum alloy material for core material / the aluminum alloy material for brazing material or the aluminum alloy material for sacrificial anode material are laminated in this order.

11. The clad material includes an intermediate layer between the core aluminum alloy material and the functional aluminum alloy material, The intermediate layer is Si: 0.05% by mass or more and 1.50% by mass or less, and Fe: 0.05% by mass or more and 2.00% by mass or less; Zn: 6.00% by mass or less, Mn: 1.80% by mass or less, Cu: 1.00% by mass or less, Cr: 0.30% by mass or less, Ti: 0.30% by mass or less, Zr: 0.30% by mass or less, V: 0.30% by mass or less, Ca: 0.30% by mass or less, Sc: 0.20% by mass or less, Ni: 0.30% by mass or less, The method for producing a clad material according to claim 6, characterized in that Mo is 0.30 mass% or less, with the balance being Al and unavoidable impurities.

Citation Information

Patent Citations

  • Method for manufacturing high-strength 1000-series aluminum alloy checkered plates

    CN102392202A

  • Brazing aluminum alloy composite pipe and production method thereof

    CN103122428A

  • Manufacturing method of high corrosion resistant aluminum alloy matching material

    JP2002066786A

  • Manufacturing method of aluminum alloy and aluminum alloy material

    JP2023116058A

  • Aluminum alloy material manufacturing method and aluminum alloy material

    JP7275336B1